Development of a multiplex PCR for identification of mastitis causing organisms - Singh, Karanvir; Chandra, Mudit; Kaur, Gurpreet; Narang, Deepti; Gupta, Dhiraj Kumar; Arora, Anil Kumar; Sharma, Narinder Singh (Indian Journal of Dairy Science, 2019)
In the present study, a de novo multiplex polymerase chain reaction using genus specific primers for four organisms’ viz., E. coli, Klebsiella pneumoniae, Staphylococcus aureus and Streptococcus agalactiae were designed to identify and differentiate all the four organisms in a single reaction. Further, DNA was extracted from mastitic milk using three different methods and was subjected to multiplex polymerase chain reaction to compare and identify the best method out of these three methods based on the amplification results of multiplex polymerase chain reaction. It was observed from the study that multiplex PCR was able to amplify three organisms (Streptococcus agalactiae, Klebsiella pneumoniae and E. coli) successfully whereas was unable to amplify Staphylococcus aureus in the multiplex PCR. Mutiplex PCR when evaluated on the field samples using mastitic milk revealed SDS Triton DNA extraction method to be superior to Power Food Microbial DNA isolation Kit and Milk Bacterial DNA isolation kit method in isolating the bacterial DNA from the mastitic milk as indicated by amplification in multiplex PCR reaction.